2012
DOI: 10.1161/circheartfailure.111.961565
|View full text |Cite|
|
Sign up to set email alerts
|

p53 Promotes Cardiac Dysfunction in Diabetic Mellitus Caused by Excessive Mitochondrial Respiration-Mediated Reactive Oxygen Species Generation and Lipid Accumulation

Abstract: Background-Diabetic cardiomyopathy is characterized by energetic dysregulation caused by glucotoxicity, lipotoxicity, and mitochondrial alterations. p53 and its downstream mitochondrial assembly protein, synthesis of cytochrome c oxidase 2 (SCO2), are important regulators of mitochondrial respiration, whereas the involvement in diabetic cardiomyopathy remains to be determined. Methods and Results-The role of p53 and SCO2 in energy metabolism was examined in both type I (streptozotocin [STZ] administration) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 32 publications
2
52
0
Order By: Relevance
“…On the other hand, the MCAD level in diabetic mice was comparable to that of nondiabetic mice of either genotype. Several previous papers reported that the mitochondrial electron transport chain is one of the major sites of ROS generation in the diabetic heart, contributing to heart malfunction (25)(26)(27)35). In contrast, other reports show that progression of diabetes does not affect the capacity of ROS generation by mitochondria (39,40).…”
Section: Fig 5 Levels Of Plin and Lipase Proteins In The Heart (A) Imentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, the MCAD level in diabetic mice was comparable to that of nondiabetic mice of either genotype. Several previous papers reported that the mitochondrial electron transport chain is one of the major sites of ROS generation in the diabetic heart, contributing to heart malfunction (25)(26)(27)35). In contrast, other reports show that progression of diabetes does not affect the capacity of ROS generation by mitochondria (39,40).…”
Section: Fig 5 Levels Of Plin and Lipase Proteins In The Heart (A) Imentioning
confidence: 98%
“…Several previous studies suggested that elevation of oxidative stress in the diabetic heart is a factor contributing to the development and progression of diabetic cardiomyopathy (17,26,35). Therefore, we examined whether the diabetes-induced increase in oxidative stress is suppressed by Plin5 deficiency by measuring MDA, a derivative of lipid peroxide (Fig.…”
Section: Fig 5 Levels Of Plin and Lipase Proteins In The Heart (A) Imentioning
confidence: 99%
“…In addition, it is known that hyperglycemia activates p53-mediated cell death in myocytes (37). p53 also promotes cardiac dysfunction in diabetic mice (115). However, p53 has a broad functional role in cells and regulates other processes, including autophagy.…”
Section: Mitophagy and P53 In Diabetesmentioning
confidence: 99%
“…This protection was associated with a decrease in myocardial lipid accumulation and complex IV induction [79]. Interestingly, pressure overload itself can lead to p53-mediated activation of the inflammatory response in adipose tissue, suggesting an interesting cross talk between the heart and peripheral adipose tissue metabolism [80••, 81••].…”
Section: Part 2 Lipotoxicity and Cardiac Functionmentioning
confidence: 99%